A study of the convection heat transfer coefficients of grinding fluids - Jin, T.; Stephenson, David J. (Technische Rundschau, Hallwag Publishers; 1999, 2008)
By using hydrodynamic and thermal modelling, the variation of the convection heat transfer coefficient (CHTC) of the process fluids within the grinding zone has been investigated. Experimental measurements of CHTC for different grinding fluids have been undertaken and show that the CHTC depends on the grinding wheel speed and the fluid film thickness within the contact zone. The film thickness is determined by grinding wheel speed, porosity, grain size, fluid type, flow rate and nozzle size. The CHTC values are compared for a wide range of grinding regimes, including HEDG, creep feed and finish grinding.